Association of Plasminogen Activator Inhibitor 1 (PAI-1) 4G/5G Polymorphism and Susceptibility to SLE in Egyptian Children and Adolescents: A Multicenter Study [Corrigendum] - Yousef AA; Mohamed FY; Boraey NF; Akeel NE; Soliman AA; Waked NM; Hashem MIA; Shehata H; Fahmy DS; Ismael A; Ibrahim LM; Ibrahim MAM; et al. (Dove Medical Press, 2021)
Yousef AA, Mohamed FY, Boraey NF, et al. J Inflamm Res. 2020;13:1103— 1111. The authors have advised the affiliation list on page 1103is incorrect. The correct author list and affiliations are asfollows: Aly A Yousef, 1 Faisal Y Mohamed, 2 Naglaa F Boraey, 3Nagwa E Akeel, 4 Attia A Soliman, 4 Nevin M Waked, 5Mustafa IA Hashem, 4 Hassan Shehata, 4 Dalia S Fahmy, 6Ali Ismael, 7 Lamya M Ibrahim, 8 Mohamed AM Ibrahim, 9Hanan F Salem, 10 Sherif M Yousry, 11 Sherif F Osman, 12Rania A Fouad, 13,14 Eman T Enan, 15 MohammedA Attia, 16,17 Mona R Afify, 18 Nancy MS Zeidan, 19Mohamed Nashat 20 Read the original article